Acting on observed social exclusion and pro-social behaviour in autism spectrum disorder. (January 2020) - Silva, Catarina; Jover, Chloé; Da Fonseca, David; Esteves, Francisco; Deruelle, Christine
Humans are commonly motivated towards cooperation and prosociality. In this study, we examined this motivational predisposition in autistic individuals. Using an adaptation of the Cyberball paradigm, we investigated subsequent pro-social behaviour after witnessing social exclusion. Participants witnessed and played a series of Cyberball games, rated their affective state and valued emotional faces with respect to their approachability. Results showed that participants from both groups were aware of the social exclusion. However, while neurotypically developing participants engaged in pro-social behaviour in reaction to the exclusion, autistic participants showed less alterations, in terms of either behaviour or affective state. The current findings suggest a distinct motivational drive and processing of social reward stimuli in autism, which may result in behavioural responses divergent from typical development when engaging in the social world.